2017
DOI: 10.1002/14651858.cd003804.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the treatment of Type 2 diabetes mellitus on the development of cognitive impairment and dementia

Abstract: We found no good evidence that any specific treatment or treatment strategy for Type 2 diabetes can prevent or delay cognitive impairment. The best available evidence related to the comparison of intensive with standard glycaemic control strategies. Here there was moderate-quality evidence that the strategies do not differ in their effect on global cognitive functioning over 40 to 60 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 69 publications
0
77
0
8
Order By: Relevance
“…In a recent study examining associations in older adults between diabetes with incident cognitive impairment, poor glycemic control and longer diabetes duration were [49]. However, a recent systematic review thought that the effect of T2DM treatment on the development of cognitive impairment and dementia still was a complex issue [50]. The relationship between glycemic control and cognitive impairment requires a larger sample and longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study examining associations in older adults between diabetes with incident cognitive impairment, poor glycemic control and longer diabetes duration were [49]. However, a recent systematic review thought that the effect of T2DM treatment on the development of cognitive impairment and dementia still was a complex issue [50]. The relationship between glycemic control and cognitive impairment requires a larger sample and longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…According to a cohort study (Ng et al, ) and a review (Dumbrill & Moulton, ), metformin and dipeptidyl peptidase 4 inhibitors (DPP4I) could exert beneficial effects on cognition among type 2 diabetes patients with normal cognition (Table S4). In contrast, a systematic review performed by Areosa Sastre, Vernooij, González‐Colaço Harmand, and Martínez () did not find any evidence that treatment of type 2 diabetes delays or prevents cognitive impairment. The results of studies investigating the effect of antidiabetic drugs on cognition in AD or MCI patients showed that DPP4I, insulin, and thiazolidinediones (TZD) were effective in increasing cognition in patients with AD or MCI (cohort studies; Isik, Soysal, Yay, & Usarel, ; Plastino et al, ; Rizzo et al, ; RCT; Craft et al, ; systematic review; Cao et al, , and meta‐analysis; Liu, Wang, & Jia, ).…”
Section: Resultsmentioning
confidence: 94%
“…Что касается лечения, направленного на снижение уровня глюкозы, рандомизированные контролируемые исследования не выявили дополнительного положительного эффекта интенсивного снижения уровня глюкозы на когнитивное функционирование пациентов с СД2 [58][59]. Cходные данные приведены в кохрейновском систематическом обзоре [5], в который в конечном итоге вошли лишь 2 исследования, где сравнивались результаты интенсивного и стандартного контроля глюкозы у больных СД2 с высоким сердечно-сосудистым риском (в общей сложности в них приняли участие 13 934 пациента). Не обнаружено статистически значимых различий между двумя режимами лечения (интенсивное снижение уровня глюкозы и стандартное) по количеству больных, у которых в конце периода наблюдения (более 5 лет) отмечалось когнитивное снижение (на 3 и более баллов по шкале Mini-Mental State Examination (MMSE)) -относительный риск (ОР) 0,98; 95% доверительный интервал (ДИ) 0,88-1,08; одно исследование; n=11,140).…”
Section: дисфункция церебральных сосудовunclassified
“…Также не выявлено различий между группами по частоте деменции (ОР 1,27; 95% ДИ 0,87-1,85; одно исследование; n=11,140). У пациентов в группе интенсивного контроля глюкозы обнаружено большее количество эпизодов тяжелой гипогликемии по сравнению с группой стандартного контроля (ОР 2,18; 95% ДИ 1,52-3,14; 2 исследования; n=12,827), что, по мнению авторов, оказало влияние на результаты [5].…”
Section: дисфункция церебральных сосудовunclassified
See 1 more Smart Citation